Pola Penggunaan Ruang Terbuka Publik di Kawasan Wisata Malioboro Pada Masa Pandemi - Suminar, Lintang; Sari, Pratiwi Anjar (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
Malioboro is the pulse of economic activity in the city of Yogyakarta. The availability of public open space to carry out various activities in Malioboro area has also become a special interest for the community and tourists besides shopping. The activities of sitting, relaxing, taking pictures, watching cultural arts events, and getting around the city by pedicab or horse cart are activities that commonly carried out by tourists in the Malioboro area. The Covid-19 pandemic that has occurred has more or less changed the condition of Malioboro. Changes and quality improvements are carried out including in public open space areas to ensure the comfort of community by adjusting various health protocols. This study aims to describe the trends in the use of Malioboro's public open space during the pandemic. The method used in this research is descriptive qualitative method. Data collection techniques are carried out through field observations and interviews with visitors and economic actors. The results showed that during the pandemic, Malioboro's public open space could not be optimal in its function as a center for interaction, social activities, and a forum for economic activity. This is due to restrictions both in the form of physical and socio-cultural activities. Keywords: Public Open Space; Malioboro; Tourism